CHEST CT SCAN FINDINGS IN A SAMPLE OF PATIENTS WITH COVID19 INFECTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Coronavirus disease 2019 (COVID-19) or severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) on January 7, 2020, was established as a source of the discovered cases, previous name was (2019-NOVAL) corona-virus (2019 nCoV), then the epidemic was termed (covid 19); Fever, fatigue, dry cough, and dyspnea, as well as a variety of chest imaging features are what COVID-19 is characterized by.